Identification of bacterial pathogens in sudden unexpected death in infancy and childhood using 16S rRNA gene sequencing - Gates, Lily; Mistry, Talisa; Ogunbiyi, Olumide; Kite, Kerry-Anne; Klein, Nigel J.; Sebire, Neil J.; Alber, Dagmar G. (Frontiers in Microbiology, 2023)
Background Sudden Unexpected Death in Infancy (SUDI) is the most common cause of post-neonatal death in the developed world. Following extensive investigation, the cause of 40% of deaths remain unknown. It is hypothesised that a proportion of deaths are due to infection that remains undetected due to limitations in routine techniques. This study aimed to apply 16S rRNA gene sequencing to post-mortem (PM) tissues from cases of SUDI, as well as those from the childhood equivalent (collectively known as Sudden Unexpected Death in Infancy and Childhood), to investigate whether this molecular approach could identify potential infection-causing bacteria to enhance the diagnosis of infection. Methods 16S rRNA gene sequencing was applied to de-identified frozen PM tissues from the Great Ormond Street Hospital diagnostic archive. Cases were grouped depending on the cause of death: (i) explained non-infectious, (ii) infectious, and (iii) unknown. Results and Conclusions In cases of known bacterial infection, the likely causative pathogen was identified in 3/5 cases using bacterial culture at PM compared to 5/5 using 16S sequencing. Where a causative bacterial pathogen was identified at routine investigation, the same organism was identified by 16S sequencing. Using these findings, we defined criteria based on sequencing reads and alpha-diversity to identify PM tissues with likely infection. Using these criteria, 4/20 (20%) cases of unexplained SUDIC were identified which may be due to bacterial infection that was previously undetected. This study demonstrates the potential feasibility and effectiveness of 16S sequencing in PM investigation to improve diagnosis of infection, potentially reducing the number of unexplained deaths and improving understanding of mechanisms.